On the pattern of interannual polar vortex–ozone co-variability during northern hemispheric winter - F. Harzer; H. Garny; H. Garny; F. Ploeger; F. Ploeger; H. Bönisch; P. Hoor; T. Birner; T. Birner (Atmospheric Chemistry and Physics, 2023)
Stratospheric ozone is important for both stratospheric and surface climate. In the lower stratosphere during winter, its variability is governed primarily by transport dynamics induced by wave–mean flow interactions. In this work, we analyze interannual co-variations between the distribution of zonal-mean ozone and the strength of the polar vortex as a measure of dynamical activity during northern hemispheric winter. Specifically, we study co-variability between the seasonal means of the ozone field from modern reanalyses and polar-cap-averaged temperature at 100 hPa, which represents a robust and well-defined index for polar vortex strength. We focus on the vertically resolved structure of the associated extratropical ozone anomalies relative to the winter climatology and shed light on the transport mechanisms that are responsible for this response pattern. In particular, regression analysis in pressure coordinates shows that anomalously weak polar vortex years are associated with three pronounced local ozone maxima just above the polar tropopause, in the lower to mid-stratosphere and near the stratopause. In contrast, in isentropic coordinates, using ERA-Interim reanalysis data, only the mid- to lower stratosphere shows increased ozone, while a small negative ozone anomaly appears in the lowermost stratosphere. These differences are related to contributions due to anomalous adiabatic vertical motion, which are implicit in potential temperature coordinates. Our analyses of the ozone budget in the extratropical middle stratosphere show that the polar ozone response maximum around 600 K and the negative anomalies around 450 K beneath both reflect the combined effects of anomalous diabatic downwelling and quasi-isentropic eddy mixing, which are associated with consecutive counteracting anomalous ozone tendencies on daily timescales. We find that approx. 71 % of the total variability in polar column ozone in the stratosphere is associated with year-by-year variations in polar vortex strength based on ERA5 reanalyses for the winter seasons 1980–2022. MLS observations for 2005–2020 show that around 86 % can be explained by these co-variations with the polar vortex.